Gut Microbiome in Impulsively Violent Female Convicts - Langmajerová, Michaela; Ježková, Janet; Kreisinger, Jakub; Semerád, Jaroslav; Titov, Ivan; Procházková, Petra; Cajthaml, Tomáš; Jiřička, Václav; Vevera, Jan; Roubalová, Radka (Neuropsychobiology, 2025)
INTRODUCTION: Impulsivity and aggression are often interlinked behavioral traits that have major implications for our society. Therefore, the study of this phenomenon and derivative interventions that could lead to better control of impulsive aggression are of interest. METHODS: We analyzed the composition and diversity of the gut bacterial microbiome of 33 impulsively violent female convicts with dissocial personality disorder and 20 non-impulsive age-matched women. Further, levels of assorted neurotransmitters and short-chain fatty acids (SCFAs) were analyzed in serum and stool samples. We also assessed all participants using a battery of psychological questionnaires and tested possible correlations between the collected clinical data and the composition and diversity of their microbiomes and metabolites. RESULTS: We identified four bacterial amplicon sequencing variants that were differentially abundant in non-impulsive versus impulsive women - the genera Bacteroides, Barnesiella, and the order Rhodospirillales were more abundant in impulsive women. In contrast, the genus Catenisphaera was more abundant in non-impulsive women. Fecal tryptophan levels were significantly higher in impulsive women. Association analysis revealed a strong positive intercorrelation between most fecal SCFAs in the entire dataset. CONCLUSIONS: Our study demonstrated possible associations between gut microbiomes and their metabolites and impulsive behavior in a unique cohort of prisoners convicted of violent assaults and a matched group of non-impulsive women from the same prison. Genus Bacteroides, which was differentially abundant in the two groups, encoded enzymes that affect serotonin pathways and could contribute to this maladaptive behavior. Similarly, increased fecal tryptophan levels in impulsive individuals could affect neuronal circuits in the brain. INTRODUCTION: Impulsivity and aggression are often interlinked behavioral traits that have major implications for our society. Therefore, the study of this phenomenon and derivative interventions that could lead to better control of impulsive aggression are of interest. METHODS: We analyzed the composition and diversity of the gut bacterial microbiome of 33 impulsively violent female convicts with dissocial personality disorder and 20 non-impulsive age-matched women. Further, levels of assorted neurotransmitters and short-chain fatty acids (SCFAs) were analyzed in serum and stool samples. We also assessed all participants using a battery of psychological questionnaires and tested possible correlations between the collected clinical data and the composition and diversity of their microbiomes and metabolites. RESULTS: We identified four bacterial amplicon sequencing variants that were differentially abundant in non-impulsive versus impulsive women - the genera Bacteroides, Barnesiella, and the order Rhodospirillales were more abundant in impulsive women. In contrast, the genus Catenisphaera was more abundant in non-impulsive women. Fecal tryptophan levels were significantly higher in impulsive women. Association analysis revealed a strong positive intercorrelation between most fecal SCFAs in the entire dataset. CONCLUSIONS: Our study demonstrated possible associations between gut microbiomes and their metabolites and impulsive behavior in a unique cohort of prisoners convicted of violent assaults and a matched group of non-impulsive women from the same prison. Genus Bacteroides, which was differentially abundant in the two groups, encoded enzymes that affect serotonin pathways and could contribute to this maladaptive behavior. Similarly, increased fecal tryptophan levels in impulsive individuals could affect neuronal circuits in the brain.
Keywords: Female; lidé středního věku; Metabolites; Bacteroides; feces; střevní mikroflóra; Humans; dospělí; Tryptophan; Neurotransmitter Agents; impulzivní chování; neurotransmiterové látky; kyseliny mastné těkavé; lidé; vězni; násilí; Impulsive Behavior; Feces; Middle Aged; Serotonin; Prisoners; Dopamine; Gastrointestinal Microbiome; ženské pohlaví; Violence; Fatty Acids, Volatile; Adult